2021
DOI: 10.1037/abn0000549
|View full text |Cite
|
Sign up to set email alerts
|

Fear conditioning in women with anorexia nervosa and healthy controls: A preliminary study.

Abstract: Anorexia nervosa is characterized by anxiety-driven behaviors, such as food avoidance and distressing persistent thoughts about weight gain and body image. The present study used a classical fear conditioning procedure to test the processes of fear acquisition and generalization, extinction, and renewal in patients with anorexia nervosa and healthy controls. An app-based fear conditioning procedure was administered remotely to 64 patients and 60 healthy controls, over two sessions. A human female scream served… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…However, the only significant interaction between group and emotion category was the one between the AN group and fear, suggesting that patients with AN are particularly impaired in the recognition of this emotion. This is consistent with previous evidence of greater impairments in specific emotions (Gramaglia et al, 2016;Leppanen et al, 2017) and with the relevance of fear in AN (Guarda et al, 2015;Lambert et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…However, the only significant interaction between group and emotion category was the one between the AN group and fear, suggesting that patients with AN are particularly impaired in the recognition of this emotion. This is consistent with previous evidence of greater impairments in specific emotions (Gramaglia et al, 2016;Leppanen et al, 2017) and with the relevance of fear in AN (Guarda et al, 2015;Lambert et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, ketamine can facilitate extinction learning, which describes the process of a new memory being formed rather than an existing memory being modified; inhibitory learning is thought to antagonise the old memory [157]. Our team found preliminary evidence for generalised impairments in extinction learning in AN [158]. It is possible that ketamine may facilitate extinction learning against feared foods and food-related situations in patients with AN.…”
Section: Neuropsychologymentioning
confidence: 85%
“…Considering various theoretical accounts implicating associative learning in AN, empirical data exploring whether individuals with AN demonstrate altered associative learning are relatively sparse. Behavioral studies using classical conditioning paradigms have demonstrated conflicting findings, with some studies suggesting that, compared to healthy control groups, those with AN may learn disgust‐related associations more quickly or have trouble unlearning/updating fear‐ and disgust‐based associations (Hildebrandt et al, 2015; Lambert et al, 2021; Olatunji, 2020), but others finding no differences in how fear‐ and disgust‐based learning may proceed (Fyer et al, 2020; Lambert et al, 2021; Olatunji, 2020). One recent investigation identified distinct AN subgroups that accounted for heterogeneous performance on a fear learning task (learning “profiles”; Fyer et al, 2020).…”
Section: Resultsmentioning
confidence: 99%